How do cardiovascular risk factors correlate with post-stroke cognitive function: Directly or indirectly through stroke severity? - Hua, Jianian; Zhou, Yixiu; Chen, Licong; Tang, Xiang; Diao, Shanshan; Fang, Qi (Frontiers in Neurology, 2022)
Objectives: Cognitive impairment may affect one-third of stroke survivors. Cardiovascular risk factors and stroke severity were known to be associated with cognitive function after stroke. However, it is unclear whether cardiovascular risk factors directly affect cognition after stroke, or indirectly affect cognition by changing stroke severity, or both. Moreover, the effect of a combination of hypertension and diabetes mellitus was conflicting. We aimed to investigate the multiple direct and indirect associations and to inspire potential intervention strategies. Materials and methods: From Feb. 2020 to Jan. 2021, 350 individuals received cognitive tests within seven days after incident stroke. Cognitive tests were performed using the Chinese version of the Mini-Mental State Examination (MMSE). A moderated mediation model was constructed to test the indirect associations between cardiovascular and demographic risk factors and cognition mediated through stroke severity, the direct associations between risk factors and cognition, and the moderating effects of hypertension and diabetes. Results: Age (estimate, -0.112), atrial fibrillation (estimate, -4.092), and stroke severity (estimate, -1.994) were directly associated with lower cognitive function after stroke. Vascular disease (estimate, 1.951) and male sex (estimate, 2.502) were directly associated with better cognition after stroke. Higher education level was associated with better cognition directly (estimate, 1.341) and indirectly (estimate, 0.227) through stroke severity. The combination of hypertension decreased the magnitude of the negative association between atrial fibrillation and cognition (estimate, from -4.092 to -3.580). Conclusions: This is the first Chinse study exploring the moderated and mediating associations between cardiovascular risk factors, stroke severity, and cognitive function after stroke. Age, female sex, and atrial fibrillation were directly associated with lower cognition after stroke. The combination of hypertension might have a positive effect on cognition.